Analisis Pengaruh Upaya Penghindaran Pajak terhadap Biaya Ekuitas pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Budi Harsono; Basten Roberto Halim (Faculty of Economics, Universitas Internasional Batam, 2020)
The purpose of this research analysis study is to explain and introduce what are the effects of tax avoidance measures on the financial costs of a company. This research was conducted using a sample of company data registered in the Indonesia Stock Exchange in the period 2013 to 2017. The sample used was 145 companies after being excluded companies that have the effect of avoiding negative taxes and financial statements that are incomplete or do not meet the criteria. The results show no significant relationship between tax avoidance with the cost of equity. Research also includes moderation variables to strengthen the relationship of tax avoidance to the cost of equity. The variable of marginal moderation of incentives, outside party supervision and information quality are proven to have an effect of increasing the effect of tax avoidance on the cost of corporate equity. This shows that there are many factors that affect the cost of equity in addition to tax avoidance. The measurement of equity costs used by CAPM is one of the equity cost measurement models that can be applied in Indonesia. So the results of these studies produce unfavorable regression results on tax avoidance efforts as measured by ETR. The results of this study only focus on Indonesia, which can only provide information benefits for Indonesian companies.